Aortic Root Replacement for Destructive Endocarditis - Clinic and Microbiology - Szczechowicz,Marcin P. (2021)
Abstract Introduction: Destructive aortic root endocarditis is associated with high mortality rates. The objective of this article was to characterize the clinical and microbiological profiles of these patients, especially concerning an already implanted aortic valve prosthesis. We also focused on prognostic factors. Methods: Eighty patients underwent aortic root replacement due to destructive endocarditis from 1999 to 2018 in our institution. We analyzed their pre, intra, and postoperative data, outcomes, and predictors of mortality. Results: Thirty-one patients had native valve endocarditis (NVE), eight patients had early-onset prosthetic valve endocarditis (PVE), and 41 patients had late-onset PVE. Streptococcus was found in 19.4% of NVE cases and no PVE case. Coagulase-negative Staphylococcus was responsible for 62.5% of the cases of early-onset PVE. Thirty-four (42.5%) patients had received inappropriate antibiotics before admission. No microorganism was associated with higher risk of mortality. Aortoventricular dehiscence was identified as an independent risk factor of mortality along with PVE, concomitant bypass surgery, and delayed diagnosis. The incidence of postoperative complications was similar in all three groups. Rates of long-term survival (P=0.044) and freedom from the composite endpoint (P=0.024) defined as death, stroke, aortic valve reinfection, and aortic valve reoperation were the lowest within the NVE group and the highest among the PVE patients. Conclusion: In endocarditis, prolonged diagnostics, inadequate antimicrobial treatment, and late surgery led to destructive local complications and worsened the prognosis. PVE is associated with higher mortality than NVE.